Representations at Work - Nielsen, Martin M. (Outlines. Critical Practice Studies, 2003)
This paper argues that “distributed cognition” facilitates a framework for studying aspects of organizations as socio-technical systems. An approach studying tool use and workflows is laid out and utilized in an analysis of information processing at a post office. Finally, some implications are presented – for organizational as well as cognitive studies. Research on performative representations is called for and, consequently, a widening of the cognition-as-computation framework is suggested.